The State, Education and Citizenship in Argentina between 1880 and 1910: Julio A. Roca and Carlos N. Vergara. Discursive Tensions around Submission or Freedom (Res Publica. Revista de Historia de las Ideas Políticas, 2022)
This work examines the conceptions of the State and of citizenship embedded in the tension between the oligarchy and Krausism in late 19th and early 20th century Argentina. The methodological approach combines genealogy and the history of philosophical ideas. First, the contradictions underlying J. A. Roca’s conception of the State are exposed, setting his liberal and natural law discourse against his authoritarian and legal positivist government practices. In contrast, C. N. Vergara’s critique of state practices under oligarchic control are presented, evidencing a Krausist natural law theological perspective -an alternative conception of the State based on democracy and harmony. Finally, Vergara’s superior understanding of the State and of citizenship is introduced, whereby freedom and organization by the people are strengthened as a means to fight the centralism and state corruption of oligarchic regimes.